Kinerja Simpang Bersinyal Jalan Ahmad Yani dengan Jalan M.Hasibuan – Jalan KH. Noer Ali Kota Bekasi - Maarif, Rizal; Nuryati, Sri; Paryati, Ninik (Universitas Islam 45, 2019)
Material construction resources are very limited, but the demand for these materials tends to increase. Therefore, it is necessary to search for alternative materials such as utilizing used goods (garbage) as construction materials. An alternative material used in this study was iron shavings waste as an additional material in the concrete brick mixture to replace sand. Therefore, it can minimize the use of sand and reduce iron shavings. The study was conducted by changing the standard size of the brick according to SNI to a size of 10 x 10 x 10 cm. The results showed that the addition of iron shavings in the concrete mixture was able to increase compressive strength value. The percentage increases in compressive strength of normal concrete blocks were: 14.87%, 24.79%, 45.45%, and 71.90%. The compressive strength of ordinary concrete brick of age 7 days is 41,374 KN, and after iron shaving addition the strength improve by 47,529 KN, 51,632 KN, 60,18 KN and 71,123 KN with the percentage of iron shaving of 2.5%, 5% , 7.5% and 10% respectively. These improve value was also categorized as quality I, II and III according to SNI 03-0349-1989 requirement.